The influence of precipitation timing and amount on soil microbial community in a temperate desert ecosystem - Xiao, Yao; Bao, Fang; Xu, Xiaotian; Yu, Ke; Wu, Bo; Gao, Ying; Zhang, Junzhong (Frontiers in Microbiology, 2023)
Introduction Global climate change may lead to changes in precipitation patterns. This may have a significant impact on the microbial communities present in the soil. However, the way these communities respond to seasonal variations in precipitation, particularly in the context of increased precipitation amounts, is not yet well understood. Methods To explore this issue, a five-year (2012–2016) field study was conducted at the northeast boundary of the Ulan Buh Desert, examining the effects of increased precipitation during different periods of the growing season on both bacterial and fungal communities. The study included five precipitation pattern treatments: a control group (C), as well as groups receiving 50 and 100% of the local mean annual precipitation amount (145 mm) during either the early growing season (E50 and E100) or the late growing season (L50 and L100). The taxonomic composition of the soil bacterial and fungal communities was analyzed using Illumina sequencing. Results After 5 years, the bacterial community composition had significantly changed in all treatment groups, with soil bacteria proving to be more sensitive to changes in precipitation timing than to increased precipitation amounts within the desert ecosystem. Specifically, the alpha diversity of bacterial communities in the late growing season plots (L50 and L100) decreased significantly, while no significant changes were observed in the early growing season plots (E50 and E100). In contrast, fungal community composition remained relatively stable in response to changes in precipitation patterns. Predictions of bacterial community function suggested that the potential functional taxa in the bacterial community associated with the cycling of carbon and nitrogen were significantly altered in the late growing season (L50 and L100). Discussion These findings emphasize the importance of precipitation timing in regulating microbial communities and ecosystem functions in arid regions experiencing increased precipitation amounts.